2008
DOI: 10.1007/s12010-008-8360-7
|View full text |Cite
|
Sign up to set email alerts
|

The Transgenic BmN Cells with Polyhedrin Gene: A Potential Way to Improve the Recombinant Baculovirus Infection Per Os to Insect Larvae

Abstract: The principle of baculovirus expression system is that substitute exogenous gene for polyhedrin (polh) gene, and the recombinant baculovirus lacks the ability to infect insect larvae by oral inoculation. In this study, we cloned the polh gene with immediate early gene 1 (ie1) promoter of Bombyx mori nucleopolyhedrovirus (BmNPV) into transposon pigA3GFP vector, transported it into BmN cells by lipofectamine and obtained the transgenic BmN cell line. The mRNA transcription of the polyhedrin gene was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, when using recombinant baculoviruses as biological pesticides, an occ+ virus could be not safe, as the subsequent generations would be able to propagate in nature. Chen et al (2009) were able to occlude Bombyx mori nucleopolyhedrovirus (BmNPV) by infection of a BmN cell line stably transformed by using a transposon-based methodology with the polyhedrin gene under the regulation of a constitutive promoter. However, the generation of a Sf9 cell line expressing polyhedrin only after AcNPV infection could be advantageous over polyhedrin constitutive expression due to the possible side-effects in cellular growth and viability.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when using recombinant baculoviruses as biological pesticides, an occ+ virus could be not safe, as the subsequent generations would be able to propagate in nature. Chen et al (2009) were able to occlude Bombyx mori nucleopolyhedrovirus (BmNPV) by infection of a BmN cell line stably transformed by using a transposon-based methodology with the polyhedrin gene under the regulation of a constitutive promoter. However, the generation of a Sf9 cell line expressing polyhedrin only after AcNPV infection could be advantageous over polyhedrin constitutive expression due to the possible side-effects in cellular growth and viability.…”
Section: Discussionmentioning
confidence: 99%
“…This novel strategy of packaging a recombinant baculovirus is convenient and safer for the inoculation of B. mori larvae. Chen et al have tried to inoculate the virus via oral inoculation [ 11 ]. However, in our study, we found that the growth of our constructed polh -expressing BmN cells seems abnormal, which may contribute to the constitutive expression of polh (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…For example, foreign proteins are usually expressed at a later stage of infection, leading to insufficient protein modification, while the invasion ability of the virus drops soon after being introduced into host cell populations [ 8 , 9 , 10 ]. More importantly, the virus vector needs to be injected into the silkworm to initiate infection and protein production because the polyhedrin gene ( polh ) has been disrupted so that no occlusion bodies could be formed to infect silkworms via oral inoculation [ 11 , 12 ]. Thus, it is necessary to construct a novel recombinant virus expression system for better performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation